Penguatan Kelembagaan perak dan Strategi Pengembangan Bisnis Berbasis Komunitas - Via Lailatur Rizki; Diana Sulianti K. Tobing; Masyhuri (CERED Indonesia Publishing, 2026)
This community service discusses institutional strengthening and business development strategy training for silver craft entrepreneurs in Pulo-Tempeh. The activity aimed to improve participants' understanding of institutional components, organizational structure, business identity, product development, pricing, SWOT analysis, and digital marketing. The method used was participatory training through material delivery, guided discussion, practical business mapping, and reflection. The novelty of the activity lies in integrating institutional strengthening with practical business strategy in one training design for silver craft micro-enterprises. The activity was held at Wayae Coffee, Pulo-Tempeh, and involved local silver entrepreneurs as participants. The results indicate increased participant awareness of the importance of structured roles, shared rules, business direction, product consistency, market adaptation, SWOT-based planning, and digital promotion. The activity concludes that silver craft businesses require both community-based institutions and market-oriented strategies to strengthen competitiveness and sustainability.